PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA TENAGA HARIAN LEPAS DI KANTOR SATPOL-PP DAERAH KOTA MANADO - MAKAUDIS, JELISTHA VICTORIA; AREROS, WILLIAM; Tampi, Johny Revo (JURNAL ADMINISTRASI PUBLIK, 2019)
To optimize the performance of the Satpol PP it is necessary to build Satpol PPInstitutions that are able to support the realization of peaceful, orderly and orderly regionalconditions. The institutional arrangement of the Satpol PP does not only consider the criteria forpopulation density in an area, but also the burden of duties and responsibilities carried out as well asthe risk of the safety of the civil servise police. For this reason, the importance of the duties andfunctions of the daily freelancers at the Satpol PP in security and law enforment in the coming timeswill be even more severe, as seen from their ability to work and motivation in their work and arrogantattitudes of daily workers Satpol PP which has work disicipline which according to the community isoften shown when carrying out its role.The purpose of this study was to find out and analyze the influence of work ability, work motivation,and work disicipline on the performance of freelance daily workers in the manado city Satpol PPOffice. The type of research used is a survey research method with a quantitative sampling so that thedata used are primary data through questionnaires with a sample of 82 daily freelancers processedwith a likert scale. The analytical tool used in this study uses SPSS21.For the results of the study at a significant lefel of 0,01% which indicaties that the results of the F testindicate there is a positive effect of work ability, work motivation, and work disicipline simultaneouslyon the performance of casual daily workers. For the t-test that has been known from the results of theanalysis that the work ability has a positive and significant effect on the performance of freelance dailyworkers in the Manado City Satpol PP Office.Based on the results of research that has been known and analyzed, it can be concluded thatwork ability has a positive and significant effect while work motivation and work discipline haveapositive and not significant coefficient of determination of work ability, work motivation and workdisicipline in explaning variable variantions in daily freelance performance are very limited. For thisreason, advice has been given to the existing institutions in the Regional Office of the Satpol PP inManado so that they must pay attention to their work ability, work motivation, and discipline byencouraging or encouraging work by providing work, work colleagues pleasant working conditions inorder to improve the performance of freelance daily workers in the Manado City Satpol PP Office.Keyword : Ability, Motivation, Discipline